2003
DOI: 10.1046/j.1365-8711.2003.06784.x
|View full text |Cite
|
Sign up to set email alerts
|

The Lyα forest around high-redshift galaxies

Abstract: Motivated by the relative lack of neutral hydrogen around Lyman‐break galaxies deduced from recent observations, we investigate the properties of the Lyα forest around high‐redshift galaxies. The study is based on improved numerical SPH simulations implementing, in addition to standard processes, a new scheme for multiphase and outflow physics description. Although on large scales our simulations reproduce a number of statistical properties of the intergalactic medium (because of the small filling factor of sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
57
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 23 publications
8
57
0
Order By: Relevance
“…The bubbles produced by galactic winds are very clearly seen in the temperature structure. Similar wind structures have been found in other simulations using the smoothed particle hydrodynamics (SPH) technique (e.g., Theuns et al 2002;Bruscoli et al 2003). The size of the hot bubbles clearly increases with the strength of the winds.…”
Section: Physical Impact Of the Winds On The Igm And The Ly Forestsupporting
confidence: 83%
See 1 more Smart Citation
“…The bubbles produced by galactic winds are very clearly seen in the temperature structure. Similar wind structures have been found in other simulations using the smoothed particle hydrodynamics (SPH) technique (e.g., Theuns et al 2002;Bruscoli et al 2003). The size of the hot bubbles clearly increases with the strength of the winds.…”
Section: Physical Impact Of the Winds On The Igm And The Ly Forestsupporting
confidence: 83%
“…Simple wind models in which LBGs were associated with massive galaxies at high redshift (Croft et al 2002;Kollmeier et al 2003aKollmeier et al , 2003bDesjacques et al 2004) have shown that gas must be affected at unrealistically large distances from galaxies to result in increased Ly transmission. More sophisticated wind model prescriptions (Croft et al 2002;Bruscoli et al 2003) do not match the observations of Adelberger et al (2003) either. Photoionization by a massive galaxy itself does not produce an intensity of ionizing radiation that is large compared to the cosmic background (Croft et al 2002;Kollmeier et al 2003a).…”
mentioning
confidence: 89%
“…Kollmeier et al (2006) found that the gas in the IGM is unaffected by the presence of winds and has only a small impact on the optical depth close to LBGs. Theuns et al (2002) and Bruscoli et al (2003) likewise found that the winds preferentially expanded into the voids, leaving the hydrogen filaments intact. It therefore seems likely that we are correctly modeling the H i around the LBGs.…”
Section: Intergalactic Metalsmentioning
confidence: 89%
“…On large scales -cubes of comoving size ∼ 13h −1 Mpc -ASSP find a clear correlation of galaxy overdensity with Lyα flux decrement, the expected signature of galaxy formation in overdense environments [37,39]. However, the observed Lyα decrement decreases within ∆ r ≈ 1h −1 Mpc of LBGs (comoving, redshift-space separation), where the simulations predict that absorption should be strongest [38,39,40]. Figure 5 illustrates this conflict.…”
Section: The Galaxy Proximity Effectmentioning
confidence: 97%
“…Only the mass-scaled and R w = 1.5h −1 Mpc models come close to matching the ASSP data. Winds that fully ionize or perfectly entrain gas to such large distances are not a natural outcome of hydrodynamic simulations with stellar feedback [43,40], and even reaching 1.5h −1 Mpc in ∼ 1 Gyr requires a sustained propagation speed ∼ 600 km s −1 . Given the challenges facing the wind explanation, it is worth considering the alternative possibility that extended Lyα emission from the target galaxies is "filling in" the corresponding region of the absorption spectrum.…”
Section: The Galaxy Proximity Effectmentioning
confidence: 99%